You can solve for y, then substitute x=-3, or you can substitute x=-3 and solve for y. Let's do it the second way first.

2x -3y = 9 (the original equation)

2(-3) -3y = 9 (equation with -3 substituted for x)

3(-2 -y) = 3*3 (factor out 3)

-2 -y = 3 (divide both sides by 3)

-y = 3 + 2 (add 2 to both sides)

y = -5 (multiply both sides by -1)

_____

Solve for y ...

2x -3y = 9

2x = 9 + 3y (add 3y to both sides)

2x -9 = 3y (subtract 9 from both sides)

(2/3)x - 3 = y (divide both sides by 3)

(2/3)(-3) -3 = y (substituted -3 for x)

-2 -3 = y (perform the multiplication)

-5 = y (perform the addition)

2x -3y = 9 (the original equation)

2(-3) -3y = 9 (equation with -3 substituted for x)

3(-2 -y) = 3*3 (factor out 3)

-2 -y = 3 (divide both sides by 3)

-y = 3 + 2 (add 2 to both sides)

y = -5 (multiply both sides by -1)

_____

Solve for y ...

2x -3y = 9

2x = 9 + 3y (add 3y to both sides)

2x -9 = 3y (subtract 9 from both sides)

(2/3)x - 3 = y (divide both sides by 3)

(2/3)(-3) -3 = y (substituted -3 for x)

-2 -3 = y (perform the multiplication)

-5 = y (perform the addition)